La metacognición como herramienta para el desarrollo de la comprensión lectora en estudiantes de colegios públicos de la ciudad de bogotá (Papeles, 2012)
This paper aims to identify the development of metacognitive processes for learning in different areas of thought in secondary education by using reading. To achieve this proposal, we begin from the explanation of the concept of metacognition, which has been used in various academic scenaries that integrate teaching – learning strategies.As teachers involved in the cognitive development of students, we believe that the proposal from the Metacognition goes beyond the limits of the classroom for generating in the student the development of autonomous learning, which reverts in the responsibility, commitment and, overall, in the intellectual and personal enrichment of the student at any scenary, becoming in the agent, manager of their own learning. For this reason, throughout the paper we develop context examples in the classroom to serve as models for teachers and students in general.The article is divided into three areas namely; introduction to the metacognition concept and its visibility in secondary education, the teacher’s role as an activator of the process, the student’s role as manager of his cognitive process and finally, the proposal to raise metacognitive awareness development in the reading comprehension.
Keywords: metacognition; reading comprehension; autonomous learning